2018
DOI: 10.5603/fm.a2017.0118
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between frontal sinus morphology and skeletal maturation

Abstract: The relationship between frontal sinus dimensions obtained from PA cephalometric radiographs and hand-wrist maturation stages suggests that frontal sinuses can be used in determining growth and development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
2
1
3
Order By: Relevance
“…Analogous findings were observed in the researches conducted on individuals of Turkey with significant results both on the right and the left sides of the frontal air sinuses. 29 A research conducted in Moradabad, India documented contrary findings to the findings of the present study. The mean area reported for the females on both the right and the left sides of frontal air sinuses documented comparatively bigger dimensions for the females as compared to the male study participants but the results were not statistically significant.…”
Section: Discussioncontrasting
confidence: 99%
“…Analogous findings were observed in the researches conducted on individuals of Turkey with significant results both on the right and the left sides of the frontal air sinuses. 29 A research conducted in Moradabad, India documented contrary findings to the findings of the present study. The mean area reported for the females on both the right and the left sides of frontal air sinuses documented comparatively bigger dimensions for the females as compared to the male study participants but the results were not statistically significant.…”
Section: Discussioncontrasting
confidence: 99%
“…The postnatal growth of human skull involves dynamic changes in size and shape of viscerocranium. It has been reported that paranasal sinuses parameters are associated with skeletal maturity [ 29 , 30 ]. Review of the literature revealed no worldwide study on the dynamics of maxillary sinus growth in children in relation to the dimensions of the middle face.…”
Section: Discussionmentioning
confidence: 99%
“…CBCT-felvételeken nemcsak a csigolyák, hanem egyéb anatómiai képletek is segítségünkre lehetnek a csontérettség meghatározásában [33][34][35][36][37][38][39][40]. Bassed munkatársaival egy a craniofacialis régió növekedése szempontjából rendkívül fontos képletnek, a sphenooccipitalis synchondrosisnak a fúzióját tanulmányozta annak érdekében, hogy a kormeghatározásban igazságügyi orvosoknak segítséget nyújtson [36].…”
Section: Háromdimenziós (3d) Képalkotó Eljárásokra éPülő Vizsgálómódsunclassified
“…A sinus frontalis morfológiája és légtartó kapacitása a növekedés során változik [38]. Vannak próbálkozások, amelyek az ezen változásokra épülő csontkormeghatározó módszereket próbáltak kifejleszteni [11,39]. Sem a sinus magasságának, sem szélességének, sem pedig e kettő hányadosának, az úgynevezett sinusindexnek sem sikerült beváltani a hozzá fűzött reményeket [11,39].…”
Section: Háromdimenziós (3d) Képalkotó Eljárásokra éPülő Vizsgálómódsunclassified
See 1 more Smart Citation